Microcredit and Poverty: When Microcredit Works and When It Doesn’t - Quibria, M.G. (Journal of Reviews on Global Economics, 2015)
This paper explores the relationship between microcredit and poverty reduction. To investigate this question, we posit a bare-bone, household model that outlines the economic environment within which various types of family- microenterprises operate. It highlights a number of issues that impinge on household earnings such as the nature of the labor market, technology, product demand and entrepreneurial skills. The paper argues that the impact of microcredit is likely to be different across household types as well as across different economic environments. The paper identifies several important demand and supply constraints to the household’s graduation from poverty. These constraints are difficult to overcome in a traditional economic environment, marked by stagnant technology and market saturation.